1996
DOI: 10.5195/jwsr.1996.93
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Levels in the Aegean Bronze Age World-System

Abstract: Aegean societies in the third and second millennia B.C. developed complex economics based on the accumulation of substantial agricultural surpluses, craft specialization, and intricate distribution systems. The trade items included both utilitarian and luxury goods. To place these activities in a proper context, this paper initially evaluates the world systems literature as it relates to antiquity. The paper then presents some specific evidence to support the contention that the Aegean BA economy was an adjunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…In Greece, landscape archaeology did emerge initially from a processual tradition that emphasized the interaction of human societies (as aggregate entities) and the natural environment to ensure subsistence and adaptive success (e.g., Kardulias 1994, p. 10: ''the interactive biological and cultural aspects of human existence within an environmental context''). But following their colleagues in the Americas and western Europe, survey archaeologists working in Greece developed varied responses to neo-evolutionism and ecological/demographic/technological determinism that in no way foregrounded environment as the decisive factor in social organization or cultural change, such as world systems theory (Kardulias 1999a(Kardulias , 1999bKardulias and Yerkes 2004), peer polity interaction (Renfrew and Cherry 1986), and annales history and other forms of structure/contingency modeling (Bintliff 1991(Bintliff , 1999Knapp 1992;Sutton 2000). One benefit of so many small surveys has been an appreciation for the surprising variability of human culture across time and space, which in turn has been instrumental in stimulating resistance to deterministic explanations in Greece as elsewhere (Trigger 1989, pp.…”
Section: Chronology and Thera Revisitedmentioning
confidence: 98%
“…In Greece, landscape archaeology did emerge initially from a processual tradition that emphasized the interaction of human societies (as aggregate entities) and the natural environment to ensure subsistence and adaptive success (e.g., Kardulias 1994, p. 10: ''the interactive biological and cultural aspects of human existence within an environmental context''). But following their colleagues in the Americas and western Europe, survey archaeologists working in Greece developed varied responses to neo-evolutionism and ecological/demographic/technological determinism that in no way foregrounded environment as the decisive factor in social organization or cultural change, such as world systems theory (Kardulias 1999a(Kardulias , 1999bKardulias and Yerkes 2004), peer polity interaction (Renfrew and Cherry 1986), and annales history and other forms of structure/contingency modeling (Bintliff 1991(Bintliff , 1999Knapp 1992;Sutton 2000). One benefit of so many small surveys has been an appreciation for the surprising variability of human culture across time and space, which in turn has been instrumental in stimulating resistance to deterministic explanations in Greece as elsewhere (Trigger 1989, pp.…”
Section: Chronology and Thera Revisitedmentioning
confidence: 98%
“…The Aegean Kardulias (1999a) used WSA to explain general trade in the Bronze Age Aegean and the production and distribution of flaked stone tools during the same period (Kardulias 1999b, d), and to analyze the results of a survey in Cyprus (Kardulias 2007;Kardulias and Yerkes 2004). Initially he suggested that the Aegean system consisted of multiple levels (internal, intermediate, and long distance) that linked local, regional, and international communities.…”
Section: Applications To European Prehistorymentioning
confidence: 99%
“…Although early works (e.g., Wallerstein 1974Wallerstein , 1980Wallerstein , 1989Braudel 1977Braudel , 1982 concentrated on the making of the capitalist world-system, the perspective has increasingly pursued a radically historical-comparative lens. Indeed, related work in worldsystems allows for pre-capitalist world-systems that were based on the urban economy and political structures (Braudel 1977;Kohl 1992;Algaze 1993;Kardulias 1996;van de Mieroop 1999). Chase-Dunn and Hall (1997) examined thousands of years and multiple societies, for instance, even allowing for world-systems of hunter-gatherers.…”
Section: A World-systems Approach To Urbanizationmentioning
confidence: 99%
“…Research on other time periods has also found evidence for world-systems prior to the advent of capitalism, even in relatively egalitarian settings (Braudel 1977;Kohl 1992;Algaze 1993;Frank and Gills 1996;Kardulias 1996;Chase-Dunn and Hall 1997). In the Fertile Crescent, networks of communities based on trade and cultural exchange are attested as early as the sixth millennium BCE, two thousand years before the rise of the Uruk system in southern Mesopotamia (Oates 1993;Blessy et al 2005).…”
Section: Networked Communitiesmentioning
confidence: 99%